2023
DOI: 10.1002/adfm.202303795
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Topology and Stereochemistry of Glycidylamine‐Derived Lipid Nanoparticles for in Vivo mRNA Delivery to Immune Cells in Spleen and Their Application for Cancer Vaccination

Mahmoud M. Abd Elwakil,
Ryota Suzuki,
Alaa M. Khalifa
et al.

Abstract: AbstractmRNA lipid nanoparticles (LNPs) have reached an inflection point and are now paving the way for a new wave of precision therapies. The design of nonhepatocyte RNA delivery systems without targeting ligands, however, remains a challenge. It is reported that the development of ligand‐free glycidylamine (GA) derivatives containing LNPs (GA‐LNPs) that preferentially deliver mRNA to immune cells in the spleen. Notably, it is demonstrated that the stereochemistry of GA‐lipids has a significant impact on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…HeLa cells treated with either stereorandom or stereoenriched hexahydrofarnesol CART-mRNA complexes showed no difference in bioluminescence (Figure S4), suggesting that the stereochemistry of the isoprenoid CART side chain has minimal effect on mRNA delivery. Other amphiphilic delivery systems where stereochemistry showed influence on transfection efficacy studied stereocenters near the charged head groups, but the hydrophobic groups possessed no stereogenic centers; therefore, these results are not inconsistent with literature reports. …”
Section: Results and Discussionsupporting
confidence: 49%
“…HeLa cells treated with either stereorandom or stereoenriched hexahydrofarnesol CART-mRNA complexes showed no difference in bioluminescence (Figure S4), suggesting that the stereochemistry of the isoprenoid CART side chain has minimal effect on mRNA delivery. Other amphiphilic delivery systems where stereochemistry showed influence on transfection efficacy studied stereocenters near the charged head groups, but the hydrophobic groups possessed no stereogenic centers; therefore, these results are not inconsistent with literature reports. …”
Section: Results and Discussionsupporting
confidence: 49%
“…Incorporation of glycinate (GA) derivatives in the LNPs (GA-LNPs) rather than the strategy of targeting ligands resulted in preferential delivery of mRNA to immune cells such as antigen-presenting cells (APCs) in the spleen. 69 Furthermore, mRNA-LNPs containing stearic acid as an additive, a well-studied compound in the realm of drug delivery, 70 were found to selectively express mRNA in the spleen following intravenous injections. 71 In addition, Daniel J. Siegwart and colleagues proved by SORT technology that anionic SORT lipids, specifically 1,2-dimyristoyl- sn -glycero-3-phosphate (sodium salt) (14PA) and sn-(3-oleoyl-2-hydroxy)-glycerol-1-phospho- sn -3’-(1′,2′-dioleoyl)-glycerol (ammonium salt) (18BMP), promoted the selective delivery of LNPs to the spleen, with 30% 1,2-dioleoyl- sn -glycero-3-phosphate (18PA) SORT LNPs demonstrating spleen-targeting potential during trials 42 …”
Section: Organ-selective Lnps As Delivery Platforms For Nucleic Acidsmentioning
confidence: 99%
“…7d). 154 Additionally, Zhao et al synthesized a poly( l -glutamic acid)-based phosphatidyl polymer (PLG-PP) and showed these phospholipid-modified polymers enabled mRNA uptake into dendritic cells and B cells within the spleen. 155 The use of hydrophobic moieties such as phospholipids coupled with high amine density polymers such as poly( l -glutamic acid) can be an attractive strategy for mRNA delivery to the spleen.…”
Section: Non-viral Mrna Delivery Strategies To the Spleenmentioning
confidence: 99%